eSurvia : a web-based survey tool using fuzzy conjoint analysis - Ayu, Media Anugerah; Ismail, Siti Aisyah; Md. Tap, Abu Osman (IIUM Press, 2011)
In the era of modem technology today, everything can be accessed in just a few clicks away, given that there are internet connection and internet accessible device. Many researchers discover this to be an added advantage to their research fields and studies, since it allows survey data collection, distribution and creation without the limitation of spatial boundary. Doing survey is not a tiring and time consuming process anymore with the availability of many free/paid web-based survey website on the internet. One thing to consider is that most of the web-based survey websites out there provide automatic analysis using normal statistics and does not allow the extraction of response data from the survey. Hence, researchers who want to use fuzzy conjoint analysis have no other options but to conduct and analyze the survey manually, which is a very tedious process to begin with. In this chapter, we will discuss on the development of eSurvia, a web-based survey tool which has the capability of providing survey analysis using fuzzy conjoint analysis and its significance